Effect of Service Quality and E-Learning Quality on Student Satisfaction in Moderation of Social Distancing During the COVID-19 Pandemic: Empirical Studies in Private Universities - Isana S. C. Meranga (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to determine the effect of service quality and e-learning quality on student satisfaction in moderation of social distancing during the coronavirus disease-19 (COVID-19) pandemic: empirical studies in Private Universities. This research is a quantitative research with a cross-sectional study survey. Collecting data through questionnaires from respondents who are active students at 3 large Private Universities in Tangerang such as Prasetya Mulya, Universitas Pelita Harapan, and Universitas Multimedia Nusantara. Respondents in this study amounted to 100 respondents. Data processing using partial least square-structural equation modeling (PLS-SEM). The results show that tangible, responsiveness, and empathy have a positive effect on e-learning quality, and e-learning quality has a positive effect on student satisfaction. Reliability and assurance do not have a positive effect on e-learning quality and furthermore social distancing does not moderate the relationship between service quality and e-learning quality. Contribution to this research provides information and knowledge for decision making, especially Private Universities through understanding service quality on quality and satisfaction in achieving competitiveness, greater value, growth in service opportunities, and satisfaction.